An audit of patients undergoing gastroscopy at Mitchells Plain District Hospital, with a focus on substance use - Mendes, Tome Azevedo (Division of General Surgery, 2024)
Background: The association between peptic ulcers and the use of crystalline methamphetamine (Tik) is often anecdotally described. While available literature describes an association with duodenal ulceration, most research is predominantly observational and the aetiology is largely unexplained. Locally, the pattern of gastrointestinal disease among methamphetamine users, as well as the manner in which they present, remains poorly understood. With an increase in the use of methamphetamine globally, a better understanding of the gastrointestinal effects of this drug is crucial. Objective: To determine the relationship between substance users and findings at index oesophagogastroduodenoscopy (OGD). Methods: A prospective, single centre audit was conducted on patients requiring elective and emergency OGD during a two month period. Baseline demographics, risk factors, nature of presentation and endoscopic findings were recorded and comparisons were made between non-users and users of methamphetamine, cannabis, mandrax and/or heroin. A subanalysis was performed on methamphetamine users. Results: 174 patients were recorded with a median age of 51.5. Ten patients were substance users, with seven patients reporting methamphetamine usage. Substance users were significantly younger (median age 38 vs 53.5; p = 0.006) and more likely to be male (90% vs 34%; p = 0.00107;X 2 2.08). Eight out of the ten substance users presented with an UGIB, significantly higher than non-users (80% vs 13.4%; p < 0.001; x 2 24.4). Substance use had a significant association with the need for inpatient endoscopy (70% vs 29.3%; p = 0.015; x 2 5.8), as well as with emergency endoscopy (50% vs 9.1%; p = 0.0005; x 2 15.9). Duodenal ulcers were confirmed in seven patients (Figure 4), with three of these occurring in substance users and resulting in a significant association (30% vs 3.45%; p = 0.0005; x 2 11.9). Conclusion: Substance users requiring OGD represented a younger, male population group that had a significant association with presenting with an upper gastrointestinal bleed and with requiring emergency, inpatient endoscopy. In keeping with available literature, a strong association with duodenal ulcers was also described. While this study has described the pattern of upper gastrointestinal disease and manner of presentation among substance users, further dedicated research is required if the underlying aetiology is to be understood.